Carpentry and Joinery : Bench and Site Skills - Porter, Brian, 1938-; Rose, Reg. (London : Arnold, 1997)
In this book, which covers the NVQ courses in Carpentry and Joinery and Bench Joinery at levels 2 and 3, the authors set out the fundamental knowledge and basic methods which recur throughout the courses.
Includes index.
Keywords: Carpentry; Joinery; House and Home